(untitled) (Numerus academy review, 2026)
Family relationships in Algerian society are categorized by simplicity, as relationship between parents and children was symbolized by the character of mutual respect and appreciation, in addition to their contribution to the application and consolidation of family values; however, these values have changed due to the new technological modernity, which is considered as double-edged weapon, seeing that it increases closeness of people, raises the degree of their interaction and creates new virtual relationships. On the other hand, it constitutes a real danger to social and family relationships, as it leads to the creation of an intellectually and educationally discordant society. That’s the change bears the factors of breaking with cultural traditions; in the light of which, this results in changing the social value system of individuals, increases the desire and tendency for loneliness and isolation, and reduces, accordingly, opportunities for realistic interaction and social dialogue within the same family.